HEALTHCARE ACCESS, QUALITY AND FINANCIAL RISK PROTECTION AMONG DISPLACED VENEZUELAN WOMEN LIVING IN BRAZIL: A CROSS-SECTIONAL STUDY - MORENO-SERRA, RODRIGO (2024)
BACKGROUND: MILLIONS OF VENEZUELANS HAVE BEEN DISPLACED BECAUSE OF DETERIORATING SOCIO-ECONOMIC CONDITIONS IN THEIR COUNTRY. WE EXAMINE KEY DOMAINS OF UNIVERSAL HEALTH COVERAGE AMONG MIGRANT VENEZUELAN WOMEN IN BRAZIL: HEALTHCARE ACCESS, CARE QUALITY AND FINANCIAL RISK PROTECTION. METHODS: WE COLLECTED PRIMARY DATA ON 2012 VENEZUELAN WOMEN AGED 15–49 WHO MIGRATED TO BRAZIL BETWEEN 2018 AND 2021, IN THE CITIES OF BOA VISTA AND MANAUS, ALONG WITH SECONDARY DATA FOR BRAZILIAN WOMEN. WE USED LINEAR REGRESSION WITH ENTROPY BALANCE MATCHING TO ESTIMATE ASSOCIATIONS BETWEEN MIGRANT STATUS AND HEALTHCARE SPENDING, UTILISATION AND QUALITY INDICATORS. FINDINGS: OUR SAMPLE HAD A MEAN AGE OF 29.5 YEARS (S.D. 8.9), 64% (1286/2011) OF MIXED ETHNICITY, 29% (577/2011) WHITE, 4% (71/2011) BLACK, 3% (62/2011) INDIGENOUS AND 1% (15/2011) OTHER ETHNICITIES. COMPARED TO BRAZILIAN WOMEN, MIGRANT WOMEN HAD 9.5 PERCENTAGE POINTS (PP) (95% CI: 6 PP–13 PP; P < 0.0001) HIGHER CATASTROPHIC HEALTH EXPENDITURE INCIDENCE. MIGRANTS WERE 27 PP (95% CI: 11 PP–43 PP; P = 0.0008) MORE LIKELY TO RECEIVE HEALTHCARE WHEN SOUGHT, BUT 37 PP (95% CI: −45 PP TO −29 PP; P < 0.0001) LESS LIKELY TO HAVE HAD A PAP SMEAR IN THE LAST THREE YEARS. MIGRANTS WERE AS LIKELY AS NON-MIGRANTS TO HAVE RECEIVED PAP SMEAR RESULTS WITHIN THREE MONTHS (95% CI: −9 PP TO 22 PP; P = 0.39) AND CLINICALLY APPROPRIATE ANTENATAL CONSULTATIONS (95% CI: −10 PP TO 40 PP; P = 0.23). INTERPRETATION: MIGRANT WOMEN IN BRAZIL HAVE RELATIVELY GOOD HEALTHCARE ACCESS AND QUALITY OUTCOMES. YET A POTENTIAL BACKLOG OF UNMET SEXUAL AND REPRODUCTIVE HEALTHCARE NEEDS AND INADEQUATE FINANCIAL RISK PROTECTION REQUIRE POLICY ATTENTION. FUNDING: UK ECONOMIC AND SOCIAL RESEARCH COUNCIL (ES/T00441X/1). © 2024 THE AUTHOR(S)